PERANCANGAN MESIN PENGGEMBUR TANAH MINI BERBANTU SOFTWARE SOLIDWORKS 2014 - Damara, Roy (Politeknik Harapan Bersama Tegal, 2023)
Abstract – One important aspect in the agricultural sector is the existence of agricultural land, tractors are tools that are often used to loosen agricultural land, diesel tractors will be quite expensive, mini tractors, smaller dimensions, farmers save costs in the process of designing the frame unit, then designing wheel unit, then the drive system, and continued to design the complete system. The purpose of this design is to determine the process of designing a mini earth crusher machine as a result of this research. The design begins with designing the frame unit, designing the wheel unit, the drive system, designing the equipment system, and continuing with stress, displacement, strain, and factor of safety analysis. In the frame section, the riskiest side is at the end with a value of 2.46 N/m² from the maximum chart of 3.07 N/m². While the wheel axle is the most risky side, namely at the end of the stress test shaft, it gets a value of 7 N/m² from the graph a maximum of 14 N/m². Furthermore, the grinding wheel gets a value of 1.3 N/m² from the graph a maximum of 15 N/m², the risky fulcrum is at the end of the bend, all parts get a value above 1 in the factor of safety test which indicates it is safe.